Strategies for Enhancing Employees’ Innovative Work Behavior: A Qualitative Study Based on Literature Review - siti musarofah; Maulidza Nur Fauzi; Nunuk Nunuk Shela Agustia; Faro Damayani (Economic and Bussiness Faculty, Dr Soetomo University, 2026)
This study aims to analyze the factors influencing innovative behavior using a Systematic Literature Review (SLR) approach. The main focus of this research is on the role of organizational justice, organizational support, and knowledge sharing in fostering innovative behavior, particularly in the context of higher education institutions. The method employed is an SLR by reviewing scientific articles published between 2020 and 2024, sourced from reputable databases such as Scopus, Sinta, and Google Scholar. The article selection process was conducted through identification, screening, eligibility, and inclusion stages. The results indicate that organizational support and organizational justice have a positive and significant impact on innovative behavior. Furthermore, knowledge sharing acts as a mediating variable that strengthens the relationship between these variables and innovative behavior. These findings suggest that a fair and supportive organizational environment, along with a strong knowledge-sharing culture, can enhance individuals’ ability to generate and implement innovative ideas. This study provides important implications for organizations, particularly higher education institutions, in designing policies that promote innovative behavior through enhancing organizational support, organizational justice, and knowledge sharing practices.